GIS and remote sensing based delineation of groundwater potential zones in a semi-arid irrigated agricultural watershed using AHP and Fuzzy-AHP - Akca, Seyma; Akyuz, Dilek Eren; Sanli, Fusun Balik (SPRINGER HEIDELBERG, 2026)
The frequency and severity of floods and droughts have increased due to climate change, along with mismanagement, and increasing demand for water resources due to population growth. Due to this increasing demand, dependence on groundwater resources has been needed unprecedentedly. In addition, overuse and unsustainable irrigation have severely stressed groundwater, which is a limited resource. This study has been used multi-criteria decision-making methods to determine the spatio-temporal variation of groundwater potential zones for ensuring effective groundwater management and security. Geographic Information Systems (GIS) and Remote Sensing (RS) technologies are used to integrate 10 thematic layers, i.e., precipitation, soil, geology, elevation, lineament density, slope, drainage density, land use/land cover (LULC), topographic wetness index (TWI), and topographic roughness index (TRI). The groundwater potential areas, with a high spatial resolution of 10 m, were delineated using the Analytic Hierarchy Process (AHP) and Fuzzy Analytic Hierarchy Process (Fuzzy-AHP) in the study area of the Harran Plain, T & uuml;rkiye. The integrity of the mapped potential zones was authenticated by well measurements and application of the Receiver Operating Characteristic (ROC) analysis, which yielded an Area Under Curve (AUC) value of 72.7% for AHP and significantly improved 97.6% for Fuzzy-AHP. The results obtained have significant implications for future efforts in mapping areas critical for sustainable groundwater use, agricultural irrigation, watershed management, and research on the relationship between groundwater dynamics and climate change, particularly in arid and semi-arid regions.
Keywords: Irrigation; AHP; Fuzzy-AHP; Harran Plain; GIS; Remote Sensing; Groundwater management; SPATIAL-RESOLUTION; FLOW DIRECTION; CLIMATE-CHANGE; RESOURCES; MODEL; ALGORITHM; RECHARGE; SYSTEMS; Agriculture